Charcot Neuroarthropathy of the Foot and Ankle - Madan, Simerjit Singh (Orthop Surg, 2013)
Charcot neuroarthropathy (CN) is a rare, progressive, deforming disease of bone and joints, especially affecting the foot and ankle and leading to considerable morbidity. It can also affect other joints such as the wrist, knee, spine and shoulder. This disease, described originally in reference to syphilis, is now one of the most common associates of diabetes mellitus. As the number of diabetics increase, the incidence of CN is bound to rise. Faster initial diagnosis and prompt institution of treatment may help to reduce its sequelae. There should be a low threshold for ordering investigations to assist coming to this diagnosis. No single investigation is the gold standard. Recent studies on pathogenesis and development of newer investigation modalities have helped to clarify the mystery of its pathogenesis and of its diagnosis in the acute phase. Various complementary investigations together allow the correct diagnosis to be made. Osteomyelitis continues to be confused with acute CN. Hybrid positron emission tomography has shown some promise in differentiating these conditions. A multispecialty approach involving diabetologists, orthopaedists and podiatrists should be used to tackle this difficult problem. The aim of this article is to describe current knowledge about CN with particular reference to the status of diagnostic indicators and management options.